Health literacy strengths and challenges of people in New South Wales prisons: a cross-sectional survey using the Health Literacy Questionnaire (HLQ) - Scott Gill; Reem Zeki; Sharlene Kaye; Panayiota Zingirlis; Vicki Archer; Amy Lewandowski; Grantley Creighton; Caron Shaw; Julia Bowman (BMC, 2023)
Abstract Background Health literacy is an important factor for enabling people to manage their health and live long fulfilling lives. People in prison are frequently from marginalised communities, often out of reach of conventional community based health organisations, and have poorer health outcomes. It is essential to understanding the health literacy profiles of people in prison, and its contribution to the well-established health inequities and outcomes of this population. This study aimed to use a multi-dimensional health literacy measurement tool to describe the strengths and challenges of adults incarcerated in NSW prisons. Methods A cross-sectional survey was conducted for people in prison across 14 publicly operated metropolitan prisons. Data were collected from 471 participants using the Health Literacy Questionnaire (HLQ). Participant characteristics and health conditions were also collected. Data were analysed using descriptive statistics. Effect sizes (ES) for standardised differences in means were used to describe the magnitude of difference between participant characteristic groups. Results Participants' median age was 38.0 (range 19 - 91) years. Males comprised 81% of the sample, 21% identified as Aboriginal and/or Torres Strait Islander, and 53% reported a health problem. People in prison had lower scores for all nine HLQ scales when compared to the general Australian population. Small to medium ES were seen for mean differences between most demographic groups. Compared to males, females had lower scores for several of the HLQ scales including 'having sufficient information to manage health' (ES 0.30 [95% Confidence Interval (CI) 0.07, 0.53]), 'ability to actively engage with health care professionals' (ES 0.30 [95% CI 0.06, 0.53]), 'navigating the healthcare system' (ES 0.30 [95% CI 0.06, 0.53]), and, 'ability to find good health information' (ES 0.33 [95% CI 0.10, 0.57]). Differing health literacy scale scores with small to medium ES were found when comparing participants by legal status. Mainly small ES were seen when comparing other participant characteristic groups. Conclusions This study provides insights into the health literacy strengths and challenges for people in NSW prisons. These findings highlight the important role health literacy could have in addressing health disparities in this vulnerable population and can inform prison health services.